Political competition and support for agriculture - Jan Fałkowski; Alessandro Olper (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
This paper investigates whether political competition plays an important role in determining the level of agricultural protection. In order to do so, we exploit variation in political and economic data from 74 developing and developed countries for the post-war period. Our results robustly show that the level of agricultural distortions is the higher, the higher is the level of political competition. We show that political competition may importantly complement other institutional aspects in determining policy choices. We investigate the heterogeneous effects of political competition across different electoral rules (majoritarian vs. proportional), forms of government (coalition vs. single-party) and level of incomes.
Keywords: D72; D78; F13; O13; P16; 330; Political competition; constitutional rules; agricultural distortions